ANALYSIS OF THE INACBG-S INPATIENT CLAIM ADMINISTRATION PROCESS BETWEEN GENERAL HOSPITALS AND SPECIAL HOSPITALS IN 2024 - AS'AD, AS'ARI; LALU, SAPARUDDIN; AMIR, ARFENTY; ASHARI, IRWAN; RAZAK, KAISAR; ARNANDHA, ATRIA GITA (Journal Medical Universitas muhammadiyah Makassar, 2026)
Background: The administrative claim process within the National Health Insurance (JKN) system managed by BPJS Kesehatan continues to experience policy dynamics that directly impact hospital claim submission mechanisms. This study aims to analyze the pending inpatient INA-CBGs claim administration process between General Hospitals (RSU) and Specialized Hospitals (RSK) during the period from July to December 2024. Methods: This study employed a quantitative approach with a cross-sectional design. Data were analyzed using the Chi-Square statistical test to determine differences in the causes of pending claims based on hospital type. Results: The findings revealed that in RSU, the dominant cause of claim pendings was related to coding rules (78%), followed by service standards (45.4%) and administrative completeness (22.8%). In RSK, although the distribution pattern differed, these three factors remained the primary contributors to claim pendings. The Chi-Square test showed no significant difference between RSU and RSK regarding service standards (p = 0.5); however, significant differences were found in coding rules and administrative completeness (p = 0.001). Conclusion: These findings indicate that hospital type influences specific aspects of the pending claim administration process. Therefore, there is a need to enhance the quality of coders in RSU through training on INA-CBGs coding guidelines, and to improve the quality of administrative personnel in RSK by recruiting staff who meet the standard educational qualifications for hospital administration.